2011
DOI: 10.1186/1742-6405-8-35
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of reference CD4+ T cell values for adult Indian population

Abstract: BackgroundCD4+ T lymphocyte counts are the most important indicator of disease progression and success of antiretroviral treatment in HIV infection in resource limited settings. The nationwide reference range of CD4+ T lymphocytes was not available in India. This study was conducted to determine reference values of absolute CD4+ T cell counts and percentages for adult Indian population.MethodsA multicentric study was conducted involving eight sites across the country. A total of 1206 (approximately 150 per/cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 22 publications
5
30
3
Order By: Relevance
“…The impact of age on CD4 ϩ and CD8 ϩ T cells and the senescence of the immune response must be studied. Regarding gender, a higher number of CD4 ϩ cells have been reported in women than in men in Indian, Spanish, and Chinese populations (4,5,9); however, in the present study, we did not find a significant difference between women and men (Table 1).…”
Section: T He Quantification Of Cd4contrasting
confidence: 56%
See 2 more Smart Citations
“…The impact of age on CD4 ϩ and CD8 ϩ T cells and the senescence of the immune response must be studied. Regarding gender, a higher number of CD4 ϩ cells have been reported in women than in men in Indian, Spanish, and Chinese populations (4,5,9); however, in the present study, we did not find a significant difference between women and men (Table 1).…”
Section: T He Quantification Of Cd4contrasting
confidence: 56%
“…In comparison to the Dutch population, Mexicans had a lower median CD4 ϩ count (11). Finally, Indian and Ugandan (19-to 24-year-old) females had a higher median CD4 ϩ count than Mexicans (4,12 ϩ cell counts and female hormone variations.…”
Section: T He Quantification Of Cd4mentioning
confidence: 99%
See 1 more Smart Citation
“…15,16 It has been suggested that a sex hormone effect could be one possible explanation for the reported higher in CD4 + T cell counts in felamle HIV/AIDS patients. 17 The number of Malassezia sp.…”
Section: Discussionmentioning
confidence: 99%
“…Immunophenotyping by flow cytometry is widely used for relative and absolute quantification of white blood cells and, therefore, it is required that laboratories establish reference ranges for relative and absolute lymphocyte subsets in peripheral blood samples [6]. Many studies have shown that different populations have distinct reference ranges [4,[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. For example, Pasqualetti et al [18] demonstrated that individuals from the Philippines have higher relative and absolute NK cell counts than Italians.…”
Section: Introductionmentioning
confidence: 99%